Training on Internet Usage as a Sales Promotion Media for Micro, Small, and Medium Enterprises (MSMEs) of Pasar Lama Community RT 01 - Yuridka, Fitrah; Ibrahim, Ibrahim; Zaenuddin, Zaenuddin (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This research addresses the impact of COVID-19 on micro, small, and medium enterprises (MSMEs) in Pasar Lama RT 01, Banjarmasin. It aims to overcome the lack of technological knowledge hindering MSMEs' growth by providing training on internet-based computerized systems for sales promotion. Method: The study employs a structured training approach, starting with explanations of computerized systems and internet utilization's effectiveness in sales promotion. Participants engage in practical sessions under team guidance, with a question-and-answer format for issue resolution. Practical Applications: By equipping MSMEs with technological skills, this research enhances their resilience and competitiveness in the face of pandemic challenges, offering practical benefits for businesses in various contexts. Conclusion: This study emphasizes the importance of technological adaptation for MSMEs, underscoring internet-based systems' role in bolstering sales promotion and business sustainability amidst crises.